Analisis Kemampuan Kognitif Siswa pada Materi Sistem Peredaran Darah Kelas XI MIA SMAN 1 Tinambung - Sufyan Hakim (Departement of Mathematics Education, 2023)
This research is a descriptive study aimed at determining the cognitive abilities of students in the process dimension and knowledge dimension based on the Revised Bloom's Taxonomy on the topic of Circulatory System for Grade XI Science students at SMAN 1 Tinambung. Understanding students' cognitive abilities is important for maximizing higher-order thinking skills (HOTS) as well as developing authentic learning plans and evaluation tools. The research instrument used was a cognitive ability test based on the Revised Bloom's Taxonomy. The research data were obtained by analyzing the Biology Lesson Implementation Plan for Grade XI Science and by administering a cognitive ability test to the students. The data analysis technique used was descriptive statistics. Based on the analysis of the Lesson Implementation Plan, the cognitive abilities taught by the teacher were as follows: C1 (Remembering) 68.75%, C2 (Understanding) 18.75%, and C4 (Analyzing) 12.50%, as well as factual knowledge 62.50% and conceptual knowledge 37.50%. The conclusion drawn from the results of the students' cognitive ability test based on the Revised Bloom's Taxonomy for multiple-choice questions is as follows: C1 (Remembering) 68.42%, C2 (Understanding) 46.05%, C3 (Applying) 21.05%, C4 (Analyzing) 60.53%, and C5 (Evaluating) 26.32%, as well as factual knowledge 57.89% and conceptual knowledge 51.32%. For essay questions, the percentage of student scores in each level is as follows: C1 40.24%, C2 53.25%, C3 58.88%, C4 51.08%, and C5 30.43%, as well as factual knowledge 52.73% and conceptual knowledge 48.19%.